The effect of lentil on cholesterol-induced changes of serum lipid cardiovascular indexes in rats - Ahmad, Mousa Numan (Progress in Nutrition, 2017)
Aim: We investigated effects of lentil on serum lipemia and cardiovascular indexes in cholesterolfed rats. Methods: Sixty male Sprague-Dawley rats were assigned into 2 groups fed diets with or without cholesterol. Diets contained casein, raw dehulled lentil, raw whole lentil, cooked dehulled lentil or cooked whole lentil and given to rats for 4 weeks. Serum total cholesterol (TC), low-density lipoprotein cholesterol (LDLC), high-density lipoprotein cholesterol (HDL-C) and triglycerides (TG) were quantified and other biological parameters were assessed. Atherogenic indexes including atherogenic index of plasma (AIP), cardiac risk ratio (CRR), atherogenic coefficient (AC), HDL-C/LDL-C and TC/TG were then calculated. Results: Cholesterol induced marked atherogenic lipemia indicated by increased LDL-C and decreased HDL-C/LDL-C. Lentil increased (p<0.05) HDL-C and thus TC and TC/TG, and decreased (p<0.05) TG and AIP, while other lipid variables or indexes were unaffected. This effect was more evident on AIP and TC/TG than lipid variables with little or no effect for different lentil diets. In all rats, lipid indexes showed mutual correlations clearly reflecting their lipid fractions and lentil-induced changes. AIP inversely linked to TC/TG (r=-0.901, p<0.0001) and both did not correlate with AC, CRR or HDL-C/LDL-C, though AC directly correlated to CRR (r=0.995, p<0.0001) and both inversely associated with HDL-C/LDL-C (r=-0.669, p<0.0001). Conclusions: Results suggest that lentil reduces AIP and increases TC/TG seemingly through its beneficial effect on TG and HDL-C regardless its form or preparation method. AIP and TC/TG perhaps provide a more distinct measure for cardioprotective effect of lentil than single lipid variables